Foreign Languages and their Impact on Income and Unemployment - Alejandro Donado (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Using a repeated cross-section of more than 258,000 residents of 39 European countries covering the period from 1990 to 2012, I study the impact of knowing different foreign languages on income and (for the first time) on unemployment. To help identify causal effects, I also employ a novel instrument based on the linguistic distance between the respondent's mother tongue and the foreign language in question. My results indicate that individuals that are able to speak foreign languages have a higher income and are less likely to be unemployed.
Keywords: Z10; J24; O52; 330